2020
DOI: 10.21273/hortsci13971-19
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Potato Minitubers under Aeroponics, Optimized for Nozzle Type and Spray Direction

Abstract: Potato seed production by conventional methods represents a sizeable investment that, when passed on to farmers, can decrease their profit margins. Potato minitubers produced by aeroponic systems are space- and cost-efficient, and they also provide healthy propagules to be used by farmers. We evaluated the effects of different misting nozzle types, with and without an antidrip feature, and spray direction on potato minituber yield using the Federal University of Viçosa (UFV) Aeroponic System. Potato pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, no published data were found that evaluate the potato morpho-physiological parameters proposed by CIP for aeroponic systems. Recently, we reported that the type of spray nozzle and the spray direction can play significant roles in several mini-potato morphological parameters and that the fogger sprayer with a downward spray at 12 L h −1 provided the highest yield of mini-tubers [7]. This modified system was used in the current study to test the morpho-physiologic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, no published data were found that evaluate the potato morpho-physiological parameters proposed by CIP for aeroponic systems. Recently, we reported that the type of spray nozzle and the spray direction can play significant roles in several mini-potato morphological parameters and that the fogger sprayer with a downward spray at 12 L h −1 provided the highest yield of mini-tubers [7]. This modified system was used in the current study to test the morpho-physiologic parameters.…”
Section: Introductionmentioning
confidence: 99%